Leukocytospermia is not an informative predictor of positive semen culture in infertile men: results from a validation study of available guidelines. Issue 3 (22nd September 2020) - Ventimiglia, Eugenio; Capogrosso, Paolo; Boeri, Luca; Cazzaniga, Walter; Matloob, Rayan; Pozzi, Edoardo; Chierigo, Francesco; Abbate, Costantino; Viganò, Paola; Montorsi, Francesco; Salonia, Andrea
Abstract: STUDY QUESTION: Are the European Association of Urology (EAU) guidelines for performing semen culture accurate enough for detecting a positive semen culture in Caucasian-European infertile men? SUMMARY ANSWER: The majority (80%) of asymptomatic infertile men with a positive sperm culture may miss a proper diagnostic assessment when relying on EAU guidelines; no single parameter can assist in medical decision-making. WHAT IS KNOWN ALREADY: The EAU guidelines suggest performing semen culture in case of increased leukocytes in semen (>10 6 peroxidase positive white blood cells/ml, i.e. leukocytospermia). STUDY DESIGN, SIZE, DURATION: A cross-sectional validation study including 523 infertile men was carried out during 2010–2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: Infertile men who were asymptomatic for genital infections were enrolled at a single academic center, and a semen culture was obtained in every case. A concentration of >10 3 cfu/ml urinary tract pathogens in the ejaculate was considered indicative of significant bacteriospermia. Semen analysis values were assessed on the basis of 2010 World Health Organization reference criteria. EAU guidelines for semen culture were used to predict positive semen culture in our cohort and thus validated. Moreover, we tested the predictive performance and accuracy of several clinical parameters and compared them to EAU guidelines. MAIN RESULTS AND THE ROLE OF CHANCE: A positive semen culture was found in 54 men (10%). The application of EAU guidelines would have missed 43 out of 54 (80%) positive semen cultures with 120/131 (92%) useless examinations. EAU guidelines specificity, sensitivity and discrimination were 74%, 20% and 47%, respectively. When trying to improve positive semen culture prediction, we were unable to find any informative baseline parameter except for serum neutrophil-to-lymphocyte ratio (odds ratio 1.70 (95% CI 1.04–2.77)), although without any improvement in terms of discrimination ( P = 0.10). LIMITATIONS, REASONS FOR CAUTION: The study was limited by the lack of a control group of fertile men its retrospective nature. Moreover, monoclonal antibodies were not used for leukocyte assessment. WIDER IMPLICATIONS OF THE FINDINGS: Since it is not possible to identify infertile men at risk of semen infection, further studies are needed to tailor the execution of semen culture. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for this study. There are no competing interests.